Antimicrobial Resistanceamong Intensive Care Unit Patients in A Tertiary Care Hospital of Bangladesh - Jesmin, Humayra; Ahasan, HAM Nazmul; Md Asaduzzaman, -; Islam, AKM Monwarul (Bangladesh Journal of Medicine, 2021)
Background: Antimicrobial resistance is a growing concern specially among the critically ill patients who are often treated by multiple antibiotics. But, the data regarding the pattern of antimicrobial resistance in this population are often insufficient. Objective: To observe the pattern of antimicrobial resistance among the patients admitted into the intensive care unit (ICU). Methodology: This prospective observational study was carried out in the ICU of a tertiary care hospital of Bangladesh over 6 months. Samples of blood, urine, tracheal aspirate, wound swab and pus were obtained from the patients, cultured and analyzed. Results: Among 100 subjects, the most common primary diagnoses were aspiration pneumonia (29%) and urinary tract infection (UTI) (24%). Out of 315 samples, microorganisms were isolated from 125 samples (39.68%). The most common sample yielding positive culture was tracheal aspirate (67.2%), and the most frequently isolated microorganisms were Pseudomonas spp. (35%), Escherichia coli (28%), Acinetobacterspp. (24%) andKlebsiellaspp. (18%). Acinetobacterspp., Pseudomonasspp. and Klebsiellaspp.were the commonest resistant organisms. Overall prevalence of resistance to antibiotics were: ceftriaxone 72%, ceftazidime 78.4%, ciprofloxacin 81.6%, gentamicin 84%, meropenem 49.6% andnetilmicin 39.2%. Meropenem was the most sensitive antibiotic against Klebsiellaspp.(66.67%) but Acinetobacterspp.was still resistant to meropenem and amikacin but sensitive to cotrimoxazole (66.67%). Multidrug resistant Pseudomonas, Acinetobacter and, Klebsiella species were found; piperacillin-tazobactam combination showed <40% resistance against them. No single antibiotic showed good efficacy against Acinetobacterspp. Conclusion: The prevalence of antibiotic resistance is high among the ICU patients, and the majority of the isolated organisms are resistant to conventional antibiotics. Bangladesh J Medicine January 2021; 32(1) : 5-11